A triarylamine-based fluorescent covalent organic framework for efficient detection and removal of Mercury(II) ion. (February 2020) - He, Yulong; Wang, Xiaomin; Wang, Kang; Wang, Limin
Abstract: A novel covalent organic framework (COF) polymer has been designed and synthesized by Suzuki polymerization of two monomers based on triarylamine derivatives, and the polymer displays nanosphere morphology due to mini-emulsion reaction system. On the basis of the above polymer, we further fabricated a Schiff base covalent organic framework polymer fluorescent sensor for efficient detection and removal of mercury(II) ions. The material underwent a fluorescence and colour change upon the touching of mercury(II) ions. Thus, taking advantage of the material to detect the presence of mercury(II) ions is quite convenient. Furthermore, the material is capable of efficiently adsorbing mercury(II) ions from aqueous solution. The fluorescence sensing device was successfully fabricated by immobilizing the polymer probe on a macroporous sponge, which was more convenient to detect and remove mercury(II) ions relative to powdery polymer probe. Graphical abstract: Image 1 Highlights: A high sensitivity, selectivity sensing material towards Hg 2+ was fabricated. Satisfactory dispersibility was achieved owing to nanoparticle morphology. The material showed low detection limit and excellent degradability for Hg 2+ . Integrated sensing device was obtained by immobilizing the material on sponge.